Identification of alternative splicing in transcript isoforms in patients with ulcerative colitis: effects of disease duration - Low, END; Wong, Z; Ngiu, CS; Nazefah, AH; Rafiz, AR; Mokhtar, N; Ali, RAR (Oxford Univ Press, 2024)
Indexed by WOS